Cold exposure triggers distinct RNA editing, alternative splicing, and gene expression patterns in cold domestication pufferfish (Takifugu obscurus) - Shuang Han; Jie Wang; Yuhao Luo; Jingping Zhang; Youquan Wang; Taixing Lin; Boyan Xu; Qigen Liu; Liangbiao Chen (Fish & Shellfish Immunology, 2026)

Adaptive Evolution for Freshwater Adaptation in Coilia nasus by Directional Selection on Osmoregulation Genes - Shuang Han; Jie Wang; Taixing Lin; Jingping Zhang; Adelino V. M. Canario; Qigen Liu; Liangbiao Chen (Molecular Ecology, 2025)
The molecular mechanisms underlying the adaptation to freshwater habitats in fish of marine origin remain unclear. Grenadier anchovies, such as Coilia nasus , originate from marine environments and include both anadromous and freshwater‐resident conspecifics, making them ideal for studying adaptive evolution from marine to freshwater habitats. We conducted a comparative population genomic and transcriptome analysis of two distinct C. nasus lineages, one anadromous and the other freshwater‐resident, collected from mainstream and estuarine regions of the Yangtze River, China. By genome‐wide genotyping of the anadromous and the freshwater‐resident populations, we observed significant divergence in osmoregulation, energy metabolism, and immune response pathways associated with ecological adaptation and energy expenditure for migration. Some ion transport genes such as CAMK1 , ATP1α3 , KCNJ1 and SLC30A2 were identified that may contribute to freshwater adaptation. Notably, numerous mineralocorticoid signalling genes (e.g., NR3C2 , SGK1 , ATP1α3 , KCNJ1 ) exhibit dynamic change between the anadromous and freshwater populations, suggesting an important role for the hormone cortisol in regulating salinity acclimation in euryhaline fish. Among these genes, the ion channel ATP1α3 experienced adaptive amino acid substitutions (Val317Ile and Thr329Ser), which appear to be evolutionary hotspots across migratory species based on ortholog comparisons. These variants may facilitate sodium/potassium transport and highlight salinity tolerance as a key driver of divergence in anadromous fish transitioning to freshwater. These results enhance our understanding of the genetic basis underlying freshwater adaptation for an anadromous fish across osmotic boundaries.